2011
DOI: 10.1007/s00198-011-1600-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum undercarboxylated osteocalcin levels are inversely associated with glycemic status and insulin resistance in an elderly Japanese male population: Fujiwara-kyo Osteoporosis Risk in Men (FORMEN) Study

Abstract: Levels of ucOC, but not iOC, were inversely associated with glycemic index and insulin resistance in a population of Japanese men. These findings will need to be confirmed with longitudinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 43 publications
10
69
1
2
Order By: Relevance
“…Metformin is known to enhance the sensitivity for insulin in several tissues showed that undercarboxylated osteocalcin levels were significantly and inversely correlated with fasting plasma glucose, HbA1c and HOMA-IR after adjusting for total osteocalcin, while total osteocalcin was not associated with these parameters after adjusting for undercarboxylated osteocalcin [60]. Thus, these findings suggest that osteocalcin may be involved in glucose metabolism not only in rodents but also in humans.…”
Section: The Association Between Osteocalcin and Glucose Metabolismmentioning
confidence: 71%
“…Metformin is known to enhance the sensitivity for insulin in several tissues showed that undercarboxylated osteocalcin levels were significantly and inversely correlated with fasting plasma glucose, HbA1c and HOMA-IR after adjusting for total osteocalcin, while total osteocalcin was not associated with these parameters after adjusting for undercarboxylated osteocalcin [60]. Thus, these findings suggest that osteocalcin may be involved in glucose metabolism not only in rodents but also in humans.…”
Section: The Association Between Osteocalcin and Glucose Metabolismmentioning
confidence: 71%
“…Clinical Study C B Confavreux and others Osteocalcin and metabolic syndrome severity 171:2that blood glucose, HbA1c, and adipokines, as well as elevated BMI or fat mass (13,14,27,28,29), were associated with serum osteocalcin. Moreover, we have previously shown that after surgical resection of osteoid osteoma in young men, serum osteocalcin level decreased, whereas blood glucose increased, thereby providing the first direct evidence of the action of osteocalcin in humans (30).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…Body mass index (BMI) was calculated as weight divided by squared height (kg/m 2 ). The assessment of insulin sensitivity was estimated by homeostasis model assessment-insulin resistance (HOMA-IR) based on FPG and insulin measurements as follows: HOMA-IR=[fasting serum insulin (mU/L)×FPG (mmol/L)]/22.5 [14] .…”
Section: Blood Measurementmentioning
confidence: 99%
“…A number of studies have evaluated the complex interactions between the skeleton and glucose and energy homeostasis in humans [7][8][9][10][11][12][13][14][15] . Osteocalcin was found to be inversely associated with fasting plasma glucose (FPG) [7,9,10] , HbA1c [7,12] , body mass index (BMI) [10,13] , fat mass [10] , measures of insulin resistance [8,14] , and measures of lipid metabolism [12,15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation